True blue baby blues: Mental health and socio-emotional wellbeing in Indigenous Australian men caring for infants and young children - D'Esposito, F; Stewart, P; Nicholson, J; Mensah, F; Giallo, R (My University, 2011)
Background: Paternal mental health and socio-emotional wellbeing (MHSEWB) are important determinants of children’s short- and long-term development and wellbeing. Research in non-Indigenous populations shows that fathers of infants are at greater risk of experiencing mental health difficulties than other men. Data on the MHSEWB of Indigenous fathers is lacking, however mental health problems have been recognised as a major difficulty for most Indigenous communities. Aim: The main aim of this study is to describe the prevalence of poor MHSEWB in Indigenous fathers with infants and young children. A secondary aim of the study is to identify factors associated with poor MHSEWB in Indigenous fathers during the first postnatal year. Methods: This study will use data from wave one of the “Baby cohort” of Footprints in Time: the Longitudinal Study of Indigenous Children. The main outcome will be MHSEWB as assessed by the “Social and Emotional wellbeing” section of the study parent questionnaire. Descriptive analyses will be used to provide socio-demographic information on the sample population and to investigate the prevalence of poor MHSEWB among Indigenous fathers. Mean MHSEWB scores will be provided to investigate associations between socio-demographic, individual, contextual, and cultural factors and poor MHSEWB in Indigenous fathers during the first postnatal year. Results and conclusions: For the first time we will report on the prevalence of poor MHSEWB in Indigenous fathers with infants and young children. Furthermore we will report on a range of risk factors that may predict poor MHSEWB in Indigenous fathers. It is likely that findings will provide guidance to better direct policy efforts to address needs that are specific to Indigenous fathers and which differ from those of their non-Indigenous counterparts.
Keywords: Health -- Mental; Gender -- Male; Gender; Health and wellbeing; Health; Gender; Male; Mental; Gender; Health and wellbeing